2010
DOI: 10.1111/j.1471-0528.2010.02746.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal morbidity and near miss in the community: findings from the 2006 Brazilian demographic health survey

Abstract: Objective To obtain an estimate of the prevalence of potentially life-threatening maternal conditions and near-miss events in Brazil, and to explore the factors associated with these complications.Design A demographic health survey (DHS) focusing on reported maternal complications.Setting Data from the five geographical regions of Brazil.Population A total of 5025 women with at least one live birth in the 5-year reference period preceding their interview in the DHS.Methods A secondary analysis of the 2006 Braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
44
4
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 14 publications
15
44
4
11
Order By: Relevance
“…Souza et al 49 comment on the limitations of the questionnaires used in this type of survey. When referring to their morbidities, women remember more of the interventions than the clinical complications; they rarely report eclampsia, for example.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Souza et al 49 comment on the limitations of the questionnaires used in this type of survey. When referring to their morbidities, women remember more of the interventions than the clinical complications; they rarely report eclampsia, for example.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies relied on the 1996 and 2006 national surveys (DHS), with home interviews of women with live births in the previous five years [48][49][50] and women with history of abortion. 51 Cecatti et al 52 used data from a vaccination campaign survey for women in the Amazon and the Northeast regions, while Rosendo and Roncalli 53 conducted a home survey in Natal City in Rio Grande do Norte State.…”
Section: Population Survey Based Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…9,15,18 Marital status was not related to SMM in most studies. 4,15,18,19 Employment status had strong association with SMM. Kayem et al 10 conducted a cohort analysis using maternal death databases on risk factors for progression from SMM to death and found that women from unemployed or routine or manual occupational groups appeared to be more likely to progress to death.…”
Section: Sociodemographic Characteristicsmentioning
confidence: 95%
“…Este estudio no encontró asociación entre morbilidad materna extrema y la convivencia con la pareja sentimental durante el embarazo, a diferencia de otros estudios que describen nueve veces más complicaciones (ic 95 %) en mujeres que no contaron con una pareja durante la gestación, comparadas con quienes sí la tuvieron (50); sin embargo, este hallazgo no ha sido consistente en la literatura publicada (45,48). Algunas observaciones destacan el papel de la madre de la gestante como una importante fuente tangible de apoyo social (56).…”
Section: Discusión Y Conclusionesunclassified